Uji Potensi Antibakteri Ekstrak Etanol Bintang Laut Linckia Laevigata Terhadap Pertumbuhan Bakteri Salmonella Typhi: ANTIBACTERIAL POTENTIAL TEST OF ETHANOL EXTRACT OF STARFISH Linckia laevigata ON THE GROWTH OF Salmonella typhi BACTERIA - Mahulauw, Muhammad Azril Hardiman; Rosita, Melia Eka; Ismayati, Dwi; Luik, Meirsia Liana (Universitas Pahlawan Tuanku Tambusai, 2025)
Linckia laevigata is a marine organism known for its potential use in traditional medicine. It contains several bioactive compounds with antibacterial properties, including alkaloids, saponins, and flavonoids. Salmonella typhi is a Gram-negative, facultatively aerobic bacterium responsible for typhoid fever. This study aimed to evaluate the antibacterial activity of the ethanol extract of L. laevigata. Extraction was performed using the maceration method for phytochemical screening, followed by the agar diffusion method to assess antibacterial activity at concentrations of 10%, 30%, and 50%. The results showed that the extract exhibited inhibitory effects at concentrations of 30% and 50%, with average inhibition zone diameters of 10.33 mm and 21.33 mm, respectively. No inhibition zone was observed at the 10% concentration. Cotrimoxazole, used as a positive control, produced an inhibition zone of 31.17 mm, while the negative control (distilled water) showed no inhibitory effect. These findings indicate that the ethanol extract of L. laevigata possesses antibacterial activity against S. typhi. Statistical analysis using one-way ANOVA revealed a p-value of > 0.012, indicating a statistically significant difference among the tested groups